Fibromatosisof Small Intestine in Children - Mahmood, .Mansoor; Akhtar, Nadeem; Hameed, Abdul; Zahir, srar; Abbasi, M. Zaheer (International Journal of Pathology, 2018)
Abstract:Fibromatosis is a rare spindle cell lesion which can at times present as tumor which is char-acterized by the remarkable proliferation and invasive growth of fibrous tissue. It often arises from the abdominal wall or the extremities and rarely from the mesentery and abdominal organs. The patient was 9 year old child with major complaints were on & off abdominal pain and mass in lower abdomen. She underwent exploratory laprotomy, with excision of mass and end to end anastomosis.